Coated high-nickel ternary positive electrode material pole piece as well as preparation method and application thereof

Through wet mixing and magnetron sputtering technology, indium doped high-nickel positive electrode material is prepared and a cladding layer is formed, which solves the problem of high-nickel ternary positive electrode material with poor capacity attenuation and poor cycle stability under high current density. Improves the circulation and rate performance of the material and enhances safety performance.

CN119133369AActive Publication Date: 2024-12-13HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202411283212.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The problem of high-nickel ternary cathode materials with poor capacity attenuation and poor cycle stability at large current density is mainly due to the degradation of electrochemical properties caused by cation mixing and microcracks.

Method used

Wet mixing and high-temperature solid phase sintering are used to prepare indium-doped high-nickel positive electrode material, and the indium-doped tungsten oxide is directly deposited on the positive electrode material sheet by magnetron sputtering to form a cladding layer to improve the material circulation performance and safety performance.

Benefits of technology

It significantly improves the circulation, rate performance and safety performance of the positive electrode sheet, reduces the mixed discharge of lithium nickel cations, increases the unit cell volume, inhibits irreversible phase change, and improves the stability and electrochemical performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a coated high-nickel ternary positive electrode material pole piece as well as a preparation method and application thereof, and belongs to the field of preparation of positive electrode materials of lithium ion batteries. The preparation method of the coated high-nickel ternary positive electrode material pole piece comprises the following steps: (1) preparing an indium-doped high-nickel positive electrode material from a high-nickel ternary precursor; (2) preparing a high-nickel ternary positive electrode material pole piece by taking the indium-doped high-nickel positive electrode material as an active substance; and (3) directly depositing indium oxide-tungsten oxide on the high-nickel ternary positive electrode material pole piece by using a magnetron sputtering method to obtain the coated high-nickel ternary positive electrode material pole piece. The preparation process is simple, surface In2O3 and WO3 and internally doped indium ions are synergistically modified, and the cycle performance, the rate capability and the safety performance of the material in battery application are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of positive electrode materials for lithium-ion batteries, and in particular to a high-nickel coated ternary positive electrode material pole piece and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics, power tools, power storage, aerospace and other fields due to their core advantages such as high energy density, high power density and high safety performance. They are currently the fastest-growing and most promising new energy storage technology, and are also an important part of balancing energy and environmental issues and promoting the realization of dual carbon goals. Among them, NCM ternary materials have extremely broad application prospects, ranging from small 3C product batteries to large electric vehicle power batteries and even future large-scale grid energy storage. They all have huge application potential. Currently, NCM has become one of the key materials in the field of power batteries. In addition, compared with LCO, NCM has another unique advantage, that is, the ratio of ternary transition metals is flexible and adjustable. The design of transition metals with different ratios allows NCM to seek a balance between high energy density and high safety performance during the development stage.

[0003] NCM ternary materials have many advantages but also some disadvantages, such as: (1) Cation mixing. Excessive nickel content is the key to cation mixing, and a high degree of cation mixing will damage the electrochemical performance of high-nickel ternary positive electrode materials and reduce the first coulomb efficiency; (2) Microcracks. Long-term charge and discharge cycles are the main cause of microcracks. Long-term charge and discharge cycles will not only cause drastic changes in lattice parameters, causing the layered structure of the material to collapse, but also cause phase changes to produce various irregular volume changes, thereby leading to the generation of microcracks, destroying the integrity of the material, aggravating the side reactions between the material and the electrolyte, increasing its impedance, and reducing the battery's discharge capacity. Summary of the invention

[0004] The purpose of the present invention is to provide a coated high-nickel ternary positive electrode material pole piece and its preparation method and application. The present invention obtains an indium-doped high-nickel positive electrode material by wet mixing and high-temperature solid-phase sintering, and then directly deposits indium oxide-tungsten oxide on the indium-doped high-nickel ternary positive electrode material pole piece by a magnetron sputtering method, thereby solving the problem of poor gram capacity attenuation and cycle stability of high-nickel ternary positive electrode materials at higher current density in the prior art.

[0005] The present invention first provides a method for preparing a high-nickel ternary positive electrode material coated electrode sheet, comprising the following steps: (1) Preparation of indium-doped high-nickel cathode material from high-nickel ternary precursor; (2) preparing a high-nickel ternary positive electrode material electrode sheet using the indium-doped high-nickel positive electrode material as an active material; (3) Using a magnetron sputtering method, indium oxide-tungsten oxide is directly deposited on the high-nickel ternary positive electrode material pole piece to obtain the coated high-nickel ternary positive electrode material pole piece.

[0006] The present invention adopts indium-doped high-nickel positive electrode material to prepare positive electrode material pole pieces, and then adopts a magnetron sputtering method to directly deposit indium oxide-tungsten oxide on the positive electrode material pole pieces, which significantly improves the cycle performance, rate performance and safety performance of the positive electrode pole pieces.

[0007] In the above-mentioned method for preparing a coated high-nickel ternary positive electrode material electrode sheet, step (1) adopts a wet mixing and high-temperature solid phase sintering process to prepare an indium-doped high-nickel positive electrode material; The high nickel ternary precursor is Ni x Co y Mn (1-x-y) (OH)2, wherein 0.75<x≤0.95, 0.05≤y≤0.2. Specifically, 0.80<x≤0.95, 0.05≤y≤0.15; more specifically, the high nickel ternary precursor is Ni 0.93 Co 0.05 Mn 0.02 (OH)2、Ni 0.90 Co 0.06 Mn 0.04 (OH)2 or Ni 0.83 Co 0.12 Mn 0.05 (OH)2.

[0008] In the above-mentioned preparation method of the coated high-nickel ternary positive electrode material electrode sheet, step (1) specifically includes the following steps: dissolving a soluble indium salt and a high-nickel ternary precursor in a solvent, adding lithium hydroxide after wet mechanical grinding, continuing to grind and then vacuum drying, and then sintering at a high temperature to obtain the indium-doped high-nickel positive electrode material.

[0009] In the above-mentioned method for preparing a high-nickel coated ternary positive electrode material electrode sheet, the soluble indium salt is indium nitrate and / or indium sulfate; The solvent is at least one of ethanol solution, anhydrous ethanol and acetone; The molar ratio of the lithium hydroxide, the high nickel ternary precursor and the soluble indium salt is 1.02:1-a:a, wherein 0<a≤0.2; specifically, 0.01≤a≤0.03; In an embodiment of the present invention, the molar ratio of the lithium hydroxide, the high nickel ternary precursor and the soluble indium salt is 1.02:0.99:0.01, 1.02:0.985:0.015 or 1.02:0.98:0.02.

[0010] The vacuum drying temperature is 80-120°C, specifically 90°C; the vacuum drying time is 10-14h, specifically 13h; The high temperature sintering is carried out in an oxygen atmosphere; The high temperature sintering is firstly kept at 500-650°C for 3-8 hours, and then heated to 780-900°C and kept for 10-18 hours.

[0011] In the above-mentioned method for preparing the coated high-nickel ternary positive electrode material electrode sheet, step (2) specifically includes the following steps: mixing the indium-doped high-nickel positive electrode material, the conductive agent, the adhesive and the dispersant to prepare a slurry, then applying it on aluminum foil, drying, pressing and cutting to obtain the high-nickel ternary positive electrode material electrode sheet.

[0012] In the above-mentioned method for preparing a high-nickel ternary positive electrode material coated electrode sheet, the conductive agent is at least one of superconducting carbon, acetylene black, conductive carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; The adhesive is at least one of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin; The dispersant is at least one of N-methyl-2-pyrrolidone, polycarboxylate (PO), polyvinylpyrrolidone (PVP) and sodium carboxymethylcellulose (CMC); Based on the total mass of the indium-doped high-nickel positive electrode material, the conductive agent and the adhesive, the mass percentage of the indium-doped high-nickel positive electrode material is 60%-95%, the mass percentage of the conductive agent is 3%-30%, and the mass percentage of the adhesive is 2%-25%.

[0013] Specifically, the mass percentage of the indium-doped high-nickel positive electrode material is 90%, the mass percentage of the conductive agent is 5%, and the mass percentage of the binder is 5%.

[0014] In the above-mentioned method for preparing a high-nickel coated ternary positive electrode material electrode sheet, in step (3), the magnetron sputtering uses an In2O3-WO3 target; specifically, based on the total mass of the In2O3-WO3 target, the mass percentage of In2O3 is 60%-90%; specifically, it can be 80%; The power of the magnetron sputtering is 50-200 W, specifically 160 W; the time is 15-40 min, specifically 20 min.

[0015] In the above-mentioned method for preparing a coated high-nickel ternary positive electrode material electrode piece, step (3) comprises the following steps: fixing the high-nickel ternary positive electrode material electrode piece on a sample stage, with the target-substrate distance set to 3-7 cm; before sputtering, the vacuum degree of the chamber is evacuated to 4×10 -4 -6×10 -4 Pa, the electrode is heated at a constant temperature to remove residual moisture and other organic matter on the electrode; the rotation rate of the electrode is set to 5-15 r / min; argon is used as sputtering gas, the gas flow rate is 20-40 sccm, and the sputtering gas pressure is 0.8-1.5Pa; after ignition, the sputtering power is 150-180 W, and the In2O3-WO3 target surface is pre-sputtered for 15-45 min to remove impurities attached to the target surface; then sputtering is performed, and the time for In2O3-WO3 coating high nickel ternary electrode is set to 15-35min to obtain the coated high nickel ternary positive electrode material electrode.

[0016] The constant temperature heating temperature is 90-120° C., specifically 110° C.; the time is 0.3-0.7 h, specifically 0.5 h.

[0017] The present invention also provides a high-nickel coated ternary positive electrode material pole piece prepared by the above preparation method.

[0018] Finally, the application of the above-mentioned coated high-nickel ternary positive electrode material electrode in the preparation of lithium-ion batteries also falls within the protection scope of the present invention.

[0019] The present invention has the following beneficial effects: (1) The present invention adopts indium doping, and the radius of indium ions is slightly larger than that of lithium ions, which effectively reduces the mixing of lithium and nickel cations and improves the order of the layered structure. At the same time, indium ions enter the lithium layer, which increases the unit cell volume and the c / a value of the lattice, widens the lithium ion transmission channel, and improves the rate performance of the material. Under high voltage, the indium ions doped in the bulk lattice lithium site bond the adjacent transition metal layer through O-In-O, which can inhibit the repulsion between oxygen layers, play a "pillar effect", reduce the irreversible phase change of the material, and improve the stability. (2) In2O3 and WO3 form a smooth coating on the surface of the electrode. The coating presents a continuous network structure composed of nanoparticles, which reduces the structural changes of the electrode during the charge and discharge cycle, inhibits HF corrosion of the electrode, and improves its room temperature cycle performance and rate performance; (3) The synergistic modification of surface In2O3, WO3 and internal doped indium ions significantly improves the cycle performance, rate performance and safety performance of the material in battery applications; (4) The overall coating of the electrode sheet provided by the present invention is a new coating method, which can play a good protective role on the electrode surface, thereby improving the electrochemical properties of the positive electrode active material, and will not hinder the transport of lithium ions or electrons inside the electrode; (5) The preparation process of the present invention is simple and the electrical performance is significantly improved. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.

[0021] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0022] The quantitative tests in the following examples were all repeated three times, and the results were averaged.

[0023] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0024] In the following examples and comparative examples, the electrochemical performance testing method is as follows: The ternary positive electrode material pole piece prepared in the embodiment and the comparative example was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the polypropylene microporous membrane was used as the separator, and 1 mol / L LiPF6 was used as the electrolyte (the solvent was a mixed solvent of EC, DEC and DMC, and the volume ratio was 1:1:1), and a CR2032 type battery was made in a glove box filled with argon. Constant current charge and discharge tests were carried out at different rates at room temperature, and the charge and discharge cut-off voltage was 2.8V~4.35V.

[0025] DSC test: 1) Fully charge the CR2032 battery and let it stand; 2) Disassemble the half-cell and scrape the positive electrode powder; 3) Spread the powder on the bottom of the crucible and add electrolyte for DSC test; Test parameters: temperature range: room temperature-400℃; heating rate: 10℃ / min; atmosphere: compressed air.

[0026] Example 1 (1) LiOH·H2O, precursor, and In(NO3)3·9H2O were weighed in a molar ratio of 1.02:0.99:0.01. First, In(NO3)3·9H2O and commercially available precursor Ni 0.93 Co 0.05 Mn 0.02(OH)2 was dissolved in anhydrous ethanol, and after wet mechanical grinding, LiOH·H2O was added to continue mechanical grinding. The mixture was vacuum dried at 90°C for 13 h, placed in a tubular furnace, and calcined at high temperature in an oxygen atmosphere. The mixture was pre-sintered at 500°C for 5 h, then heated to 850°C for 14 h, and then cooled to obtain an indium-doped high-nickel positive electrode material.

[0027] (2) The indium-doped high-nickel positive electrode material prepared in step (1) is used as the active material, SP (conductive carbon black) is used as the conductive agent, PVDF (polyvinylidene fluoride) is used as the binder, and N-methyl-2-pyrrolidone (NMP) is used as the dispersant. The slurry is prepared according to the mass ratio of active material: SP: PVDF = 90:5:5, and the slurry is applied on aluminum foil, dried, pressed, and cut to obtain a high-nickel ternary positive electrode material electrode sheet.

[0028] (3) The target material used was a commercial In2O3-WO3 target (Jiangxi Kete New Materials Co., Ltd., target material specifications: In2O3 (80%)-WO3 (20%) wt%, purity 99.95%, diameter 50 mm*thickness 3 mm). The high nickel ternary positive electrode material electrode prepared in step (2) was mounted on the substrate clamp, sent into the chamber and fixed on the sample stage, and the target-substrate distance was set to 5 cm; before the sputtering experiment, the vacuum degree of the chamber was evacuated to 5×10 -4 Pa, the electrode is heated at a constant temperature of 110°C for 0.5 h to remove residual moisture and other organic matter on the electrode, and the rotation rate of the electrode is set to 10 r / min to ensure the uniformity of film formation; argon (purity: 99.999%) is used as sputtering gas, the gas flow rate is 30 sccm, and the sputtering pressure is 1 Pa; after ignition, the sputtering power is 160 W, and the surface of the In2O3-WO3 target is pre-sputtered for 30 min to remove impurities attached to the target surface; then sputtering is performed, and the time for In2O3-WO3 coating high nickel ternary electrode is set to 20 min to obtain a electrode coated with high nickel ternary positive electrode material.

[0029] Example 2 The preparation method is the same as that of Example 1, except that the molar ratio of LiOH·H2O, precursor and In(NO3)3·9H2O in step (1) is changed to 1.02:0.985:0.015 to obtain a high-nickel coated ternary positive electrode material electrode.

[0030] Example 3 The preparation method is the same as that of Example 1, except that the molar ratio of LiOH·H2O, precursor and In(NO3)3·9H2O in step (1) is changed to 1.02:0.98:0.02 to obtain a high-nickel coated ternary positive electrode material electrode.

[0031] Example 4 The precursor used in Example 1 was replaced by Ni 0.90 Co 0.06 Mn 0.04 (OH)2, and other synthesis conditions are the same as those in Example 1 to obtain a high-nickel coated ternary positive electrode material electrode.

[0032] Example 5 The precursor used in Example 1 was replaced by Ni 0.83 Co 0.12 Mn 0.05 (OH)2, and other synthesis conditions are the same as those in Example 1 to obtain a high-nickel coated ternary positive electrode material electrode.

[0033] Comparative Example 1 (Unmodified High Nickel Ternary Positive Electrode Material Pole Plate) (1) According to the molar ratio of LiOH·H2O to precursor of 1.02:1, the commercially available precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was dissolved in anhydrous ethanol, and after wet mechanical grinding, LiOH·H2O was added to continue mechanical grinding. The mixture was vacuum dried at 90°C for 13 h, placed in a tubular furnace, and calcined at high temperature in an oxygen atmosphere. The mixture was pre-sintered at 500°C for 5 h, then heated to 850°C for 14 h, and then cooled to obtain an undoped high-nickel positive electrode material.

[0034] (2) The undoped high-nickel positive electrode material of step (1) is used as the active material, SP is used as the conductive agent, PVDF is used as the binder, and N-methyl-2-pyrrolidone (NMP) is used as the dispersant. The slurry is prepared according to the mass ratio of undoped high-nickel positive electrode material: SP: PVDF = 90:5:5, and the slurry is applied on aluminum foil for drying, pressing, and cutting to obtain an undoped high-nickel ternary positive electrode material electrode sheet.

[0035] Comparative Example 2 (Indium-doped high-nickel ternary positive electrode material electrode) Without step (3) of Example 1, other synthesis conditions are the same as those of Example 1, and an indium-doped high-nickel ternary positive electrode material electrode sheet is obtained.

[0036] Comparative Example 3 (coated undoped high nickel ternary positive electrode material pole piece) Except for weighing LiOH·H2O and precursor in a molar ratio of 1.02:1 in step (1), other synthesis conditions are the same as those in Example 1, and a coated undoped high-nickel ternary positive electrode material electrode is obtained.

[0037] Table 1 Summary of electrical properties of button cells prepared from positive electrode material sheets prepared in Examples and Comparative Examples

[0038] Table 1 is a summary table of the electrical properties of button cells prepared from the positive electrode material plates prepared in the examples and comparative examples. It can be seen from Table 1 that the positive electrode material plates prepared in Examples 1-3 have advantages in the first discharge specific capacity compared with the unmodified high-nickel ternary positive electrode material plates in Comparative Example 1 and the indium-doped high-nickel ternary positive electrode material plates in Comparative Example 2, and also have good capacity retention after 100 cycles. When the molar ratio of the precursor to In(NO3)3·9H2O is 0.985:0.015, the electrochemical performance of the high-nickel ternary positive electrode plate is significantly improved, so Example 2 is the best example, indicating that the coated high-nickel ternary positive electrode plate provided by the present invention has better electrochemical performance.

[0039] Table 2 Summary of electrical properties of button cells prepared from positive electrode material sheets prepared in Example 2 and Comparative Example 1

[0040] Table 2 shows the DSC performance of button cells made of the positive electrode material pole pieces prepared in Comparative Example 1 and Example 2 of the present invention, with a button voltage range of 2.8-4.35V; the peak decomposition temperature of Example 2 is 208.45°C, and the peak decomposition temperature of Comparative Example 1 is 200.93°C, which is increased by 7.52°C, and the safety performance is improved.

Claims

1. A method for preparing a high-nickel ternary positive electrode material electrode sheet, characterized in that: The steps include: (1) Preparation of indium-doped high-nickel cathode material from high-nickel ternary precursor; (2) preparing a high-nickel ternary positive electrode material electrode sheet using the indium-doped high-nickel positive electrode material as an active material; (3) Using a magnetron sputtering method, indium oxide-tungsten oxide is directly deposited on the high-nickel ternary positive electrode material electrode piece to obtain the coated high-nickel ternary positive electrode material electrode piece.

2. The method for preparing a high-nickel ternary positive electrode material coated electrode sheet according to claim 1, characterized in that: Step (1) preparing an indium-doped high-nickel positive electrode material by wet mixing and high-temperature solid phase sintering process; The high nickel ternary precursor is Ni x Co y Mn (1-x-y) (OH)2, wherein 0.75<x≤0.95, 0.05≤y≤0.

2.

3. The method for preparing a high-nickel ternary positive electrode material coated electrode sheet according to claim 2, characterized in that: Step (1) specifically comprises the following steps: dissolving a soluble indium salt and a high-nickel ternary precursor in a solvent, adding lithium hydroxide after wet mechanical grinding, continuing grinding and vacuum drying, and then sintering at a high temperature to obtain the indium-doped high-nickel positive electrode material.

4. The method for preparing a high-nickel ternary positive electrode material coated electrode sheet according to claim 3, characterized in that: The soluble indium salt is indium nitrate and / or indium sulfate; The solvent is at least one of ethanol solution, anhydrous ethanol and acetone; The molar ratio of the lithium hydroxide, the high nickel ternary precursor and the soluble indium salt is 1.02:1-a:a, wherein 0<a≤0.2; The vacuum drying temperature is 80-120°C; the vacuum drying time is 10-14 h; The high temperature sintering is carried out in an oxygen atmosphere; The high temperature sintering is firstly kept at 500-650°C for 3-8 hours, and then heated to 780-900°C and kept for 10-18 hours.

5. The method for preparing a high-nickel ternary positive electrode material coated electrode sheet according to claim 1, characterized in that: Step (2) specifically includes the following steps: mixing the indium-doped high-nickel positive electrode material, a conductive agent, an adhesive and a dispersant to prepare a slurry, then applying the slurry on an aluminum foil, drying, pressing and cutting the slurry to obtain the high-nickel ternary positive electrode material electrode sheet.

6. The method for preparing a high-nickel ternary positive electrode material coated electrode sheet according to claim 5, characterized in that: The conductive agent is at least one of superconducting carbon, acetylene black, conductive carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; The adhesive is at least one of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin; The dispersant is at least one of N-methyl-2-pyrrolidone, polycarboxylate, polyvinylpyrrolidone and sodium carboxymethyl cellulose; Based on the total mass of the indium-doped high-nickel positive electrode material, the conductive agent and the adhesive, the mass percentage of the indium-doped high-nickel positive electrode material is 60%-95%, the mass percentage of the conductive agent is 3%-30%, and the mass percentage of the adhesive is 2%-25%.

7. The method for preparing a high-nickel ternary positive electrode material coated electrode sheet according to claim 1, characterized in that: In step (3), the magnetron sputtering uses an In2O3-WO3 target; The power of the magnetron sputtering is 50-200 W, and the time is 15-40 min.

8. The method for preparing a high-nickel ternary positive electrode material coated electrode sheet according to claim 7, characterized in that: Step (3) comprises the following steps: fixing the high nickel ternary positive electrode material electrode on the sample stage, and setting the target-substrate distance to 3-7 cm; before sputtering, pumping the vacuum degree of the cavity to 4×10 -4 -6×10 -4 Pa, the electrode is heated at a constant temperature to remove residual moisture and other organic matter on the electrode; the rotation rate of the electrode is set to 5-15 r / min; argon is used as sputtering gas, the gas flow rate is 20-40 sccm, and the sputtering pressure is 0.8-1.5 Pa; after ignition, the sputtering power is 150-180 W, and the In2O3-WO3 target surface is pre-sputtered for 15-45 min; then sputtering is performed, and the time for In2O3-WO3 coating high nickel ternary electrode is set to 15-35min to obtain the coated high nickel ternary positive electrode material electrode.

9. A high-nickel coated ternary positive electrode material electrode prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the coated high-nickel ternary positive electrode material electrode sheet according to claim 9 in the preparation of lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of indium-doped lithium nickel cobalt manganate material

    CN111072074A

  • Lithium indium oxide coated indium-doped high-nickel positive electrode material and preparation method thereof

    CN113206237A

  • Lithium titanate / titanium dioxide coated ternary positive pole piece as well as preparation method and application thereof

    CN117080366A

  • Positive electrode material and preparation method thereof, positive electrode plate, lithium ion battery and electric equipment

    CN117954608A

  • Electrode materials

    US20110294006A1

Cited By

  • Co-coated positive electrode material with SEI-like film coating layer and preparation method of co-coated positive electrode material

    CN121546024A